(untitled) (Brazilian Journal of Health Research, 2024)
The 1st HUCAM Congress on Teaching, Research, Extension, and Innovation (CONPEI), held on November 28–29, 2024, had as its central theme “Integration as a strategy for excellence in health care.” The event represented a milestone for the academic and health professional community in Espírito Santo, fostering dialogue among institutions, services, and knowledge, with the aim of strengthening teaching practices, scientific research, university extension, and technological innovation. With the participation of state authorities, representatives from the Federal University of Espírito Santo (Ufes) and Ebserh’s top governance, as well as guest professors, health professionals, residents, and students, the congress brought together different perspectives around a common goal: to enhance hospital and outpatient care and broaden the social impact of HUCAM-Ufes initiatives. The activities were structured around round tables, lectures, workshops, and scientific sessions, covering key thematic areas: Care: integration of Ebserh Network hospitals and their impact on public health; care lines such as obesity; and health simulation as a teaching-learning strategy in different care settings. Extension: experiences of university integration and the social impact of projects developed in collaboration with communities. Research: advances in translational research within the Ebserh Network; HUCAM’s participation in prominent studies in the fields of infectious diseases, cardiology, women’s health, rheumatology, and oncology. Innovation: implementation of transformative methodologies in teaching, care, and digital education, along with discussions on emerging technologies applied to health. The congress also featured thematic workshops, oral communication sessions, and poster presentations, which enabled a wide exchange of experiences among researchers, professionals, and students. The event concluded with the awarding of the three best works, recognized in the fields of research, innovation, and extension, in a ceremony that highlighted the quality of the contributions and the academic community’s commitment to excellence in health. The texts gathered in these Proceedings thus reflect the plurality of perspectives, experiences, and contributions that marked CONPEI, offering the reader not only the abstracts of the presented works but also the extended versions of the studies awarded by the scientific committee. It is hoped that this record will serve both as a memory of the event and as an encouragement for the continuity of integrated actions in pursuit of excellence in health care.